The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.33369/jeet.2.2.83-92
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clustering Technique on Students’ Writing Ability

Abstract: The research was aimed to investigate whether clustering technique can affect students’ writing ability. The research was conducted at the first year students of Senior High School number 8 Bengkulu. In conducting the research, the researcher applied a quasi experiment method with MIA 2 and MIA 1 as the sample. MIA 2 as an experimental group that consist of 24 students was taught by using clustering technique and MIA 1 as a control group that consist of 26. They were taught by conventional technique. Both of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When clustering technique was used in the experimental class, most of students felt happy and enjoyed in writing recount text while some of them felt lazy in making the cluster diagram. The clever students are even more challenged to make a good cluster diagram from ideas in their mind and write their ideas in writing [19]- [22]. They were so busy at expressing, transferring, and associating their thoughts by using clustering technique.…”
Section: Resultsmentioning
confidence: 99%
“…When clustering technique was used in the experimental class, most of students felt happy and enjoyed in writing recount text while some of them felt lazy in making the cluster diagram. The clever students are even more challenged to make a good cluster diagram from ideas in their mind and write their ideas in writing [19]- [22]. They were so busy at expressing, transferring, and associating their thoughts by using clustering technique.…”
Section: Resultsmentioning
confidence: 99%
“…Second, some other studies focus on the effect of the clustering technique to increase students' ability in English writing. These studies were quasi-experiment (Dewi & Ayunisa, 2020;Hanafiawi, Muharam, & Parmawati, 2020;Sumartini, Puspita, & Zahrida, 2018). Sumartini et al (2018) showed that the clustering technique affects students' writing ability.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were quasi-experiment (Dewi & Ayunisa, 2020;Hanafiawi, Muharam, & Parmawati, 2020;Sumartini, Puspita, & Zahrida, 2018). Sumartini et al (2018) showed that the clustering technique affects students' writing ability. It shows that the tcount was 2.07 and the t-table was 2.01.…”
Section: Introductionmentioning
confidence: 99%